Capacity Analysis of Channel Models for Different Environments at 28/39 GHz With NYUSIM - Kola, A.F.; Kurnaz, C. (Institute of Electrical and Electronics Engineers Inc., 2022)
With the implementation of 5G, new frequencies, shorter distances between antennas, different lines of sight, and changing path loss parameters affect communication efficiency depending on the communication environment. In this study, the effect of channels created in different environments for 28 GHz and 39 GHz frequencies and LOS/NLOS conditions on 5G channel capacity was investigated using the NYUSIM channel simulator. As a result of the analyses, it has been discussed which channel parameters can be used to optimize communication efficiency in different environments. © 2022 IEEE.
Keywords: 5G; Channel Capacity; Channel Modeling; MmWave; NYUSIM